Pengaruh Gaya Kepemimpinan Transaksional Dan Transformasional Terhadap Kinerja Karyawan Yang Di Mediasi Oleh Motivasi Kerja - Jajak Sadam Bin Abai Duru; Khalikussabir Khalikussabir; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract This study aims to determine the direct and indirect effects of transactional and transformational leadership on employee performance, with motivation as a mediator. This study uses a quantitative method with an explanatory research approach by conducting a questionnaire survey of respondents. The research hypothesis was tested using multiple linear regression and path analysis tests.The conclusions of this study are (1) transactional leadership and transformational leadership  have an effect on motivation. (2) Transactional leadership style and work motivation cannot influence employee performance, but transformational leadership style can influence employee performance. (3) Work motivation cannot mediate the relationship between transactional leadership and transformational leadership on employee performance. Keywords : Transactional Leadership, Transformational Leadership, Motivation, Employee Performance.